PEMBERDAYAAN PERAJIN TEMPE DALAM MENGEMBANGKAN SENTRA INDUSTRI KECIL TEMPE DI KOTA SEMARANG - Rusdarti, R (Semarang State University, 2011)
The presence of small craft industries tempe, is one of the economic pillars of the people who can provide added value economy in the city, as well as providing a significant contribution in expanding employment opportunities, as well as a force capable of improving the welfare of the people. The purpose of this study to describe the phenomenon of small industrial/tempe producers, potential and constraints of the economic empowerment of communities that can be applied and developed in a small industrial tempe, and formulate policies in accordance with the potential srategi small craft industries tempe in the city of Semarang. The results showed that: 1) The tendency of the phenomenon of changes in tempe crafter business patterns are relatively small and micro enterprises as well as conditions of low-quality human resources, which lead them to be low income, (2) Empowerment has changed the concept of economic and social development that has the potential of productive micro-economic basis. Factors expertise/ skill used in the production process significantly contributed 67.8 percent of industrial production on a small tempe. It shows the contribution of the most dominant in the small industrial tempe, that expertise is important in a small industrial tempe, (3) development strategy capable of mobilizing the various aspects of resources and the capacity and potential of the community, making empowerment can be implemented into the best tools in an effort to income artisans tempe city of Semarang. Recommended considering internal factors crafters tempe still weak and fundamentally, the crafters need to get guidance and the way in which one of them by learning from the experience and the concerns of various stakeholders.Keberadaan industri kecil perajin tempe, merupakan salah satu pilar ekonomi rakyat yang mampu memberikan nilai tambah ekonomi di Kota Semarang, serta memberikan sumbangan yang signifikan dalam memperluas lapangan kerja, sekaligus menjadi kekuatan yang mampu meniingkatkan kesejahteraan rakyat. Tujuan penelitian ini untuk mendeskripsikan fenomena industri kecil/perajin tempe, potensi dan kendala pemberdayaan ekonomi masyarakat yang dapat diaplikasikan dan dikembangkan dalam industri kecil tempe, serta merumuskan srategi kebijakan sesuai dengan potensi industri kecil perajin tempe di Kota Semarang. Hasil penelitian menunjukkan bahwa: (1) Kecenderungan fenomena perubahan yang terjadi pada perajin tempe pola usahanya yang relatif kecil dan mikro serta kondisi sumberdaya manusia rendah kualitasnya, yang mengakibatkan pendapatan mereka menjadi rendah, (2) Pemberdayaan telah mengubah konsep pembangunan ekonomi dan sosial yang memiliki potensi dasar ekonomi mikro produktif. Faktor keahlian/skill yang digunakan dalam proses produksi secara signifikan memberikan kontribusi sebesar 67,8 persen terhadap hasil produksi pada industri kecil tempe. Ini menunjukkan kontribusi yang paling dominan dalam industri kecil tempe, artinya keahlian menjadi penting dalam industri kecil tempe, (3) Strategi pengembangan mampu memobilisasi berbagai aspek sumber daya serta kapasitas dan potensi masyarakat, sehingga pemberdayaan dapat diimplementasikan menjadi alat terbaik sebagai upaya untuk peningkatan pendapatan perajin tempe Kota Semarang. Disarankan mengingat faktor internal perajin tempe masih lemah dan mendasar, para perajin perlu mendapat bimbingan dan cara yang ditempuh salah satunya dengan belajar dari pengalaman dan adanya kepedulian dari berbagai pihak terkait.